2019
DOI: 10.1186/s12879-019-3830-9
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of paired samples for the Serodiagnosis of toxoplasmosis infection in a tertiary teaching Hospital in Malaysia

Abstract: Background Accurate diagnosis of Toxoplasma gondii ( T. gondii) infection remains elusive and requires a comprehensive assessment through laboratory and clinical investigation. In this study, a diagnostic algorithm based on paired serum samples and clinical data was developed and evaluated. Methods A total of 1267 suspected cases of Toxoplasma infection were enrolled in this study from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The clinician could not differentiate early, active, latent, chronic, congenital, or reactivated infection from serological assays, such as latex agglutination assay (LAT), immunochromatographic techniques (ICT), and enzyme linked immunosorbant assay (ELISA) (Table 7), which are used for qualitative and quantitative detection of IgM and IgG antibodies, but cannot differentiate between acute and chronic persistent infection of T. gondii parasite. Contreras [45] and Thangarajah et al [46] also support our views and stated that it always remained a diagnostic challenge for clinicians, while Liu et al [47] and Grzybowski et al [48], suggested development of specific molecular markers for clinical differentiation of acute stage of T. gondii infection from chronic stages. The asymptomatic and chronic nature of T. gondii infection poses various diagnostic, therapeutic and preventive challenges.…”
Section: Discussionsupporting
confidence: 75%
“…The clinician could not differentiate early, active, latent, chronic, congenital, or reactivated infection from serological assays, such as latex agglutination assay (LAT), immunochromatographic techniques (ICT), and enzyme linked immunosorbant assay (ELISA) (Table 7), which are used for qualitative and quantitative detection of IgM and IgG antibodies, but cannot differentiate between acute and chronic persistent infection of T. gondii parasite. Contreras [45] and Thangarajah et al [46] also support our views and stated that it always remained a diagnostic challenge for clinicians, while Liu et al [47] and Grzybowski et al [48], suggested development of specific molecular markers for clinical differentiation of acute stage of T. gondii infection from chronic stages. The asymptomatic and chronic nature of T. gondii infection poses various diagnostic, therapeutic and preventive challenges.…”
Section: Discussionsupporting
confidence: 75%
“…Previous literatures showed that the presence of Toxoplasma IgG titer in a newborn without significant four-fold increment could be due to passive transfer of maternal toxoplasma IgG from the placenta. 19,20 In terms of clinical presentations, bilateral cataracts are commonly due to several causes, such as TORCH infection and prematurity, seen in the second patient. 21 CMV viral load is important before starting preemptive therapy and after completed treatment for monitoring response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasma gondii , an obligate intracellular protozoan parasite ubiquitous worldwide, is of medical and veterinary importance because it can cause toxoplasmosis that threatens warm-blooded animals and human health [ 21 ]. More than 30% of the world’s population is thought to have specific anti- T. gondii antibodies, though infection rates vary considerably by geographic region [ 26 ]. In China, antibody-positive rates for T. gondii were described to be 8.20% in the general population and 8.60% in pregnant women [ 11 ].…”
Section: Introductionmentioning
confidence: 99%